Smart contracts as interoperability bridges: a literature review of blockchain integration and cross-chain communication - Rosdi, Nur Nisa Humairah; Amerolazuam, Amysha Qistina; Ahmadzamani, Nur Zafirah Adira; Zainuddin, Ahmad Anwar (IIUM Press, 2025)
This concise review paper discusses the application of smart contracts to increase blockchain interoperability. The emergence of blockchain has opened many opportunities to explore the advantage of modern technology. Blockchain networks operate as isolated ecosystems, hindering the seamless transfer of assets and data across different platforms. This ecosystem leads to the inability to interact or communicate within the blockchain. Smart contracts present a promising solution for facilitating interoperability between blockchains. In this paper,the potential of smart contracts as bridge technologies between blockchains is explored. The design and implementation of smart contracts to enable secure,trust less communication and asset transfer between disparate blockchain networks are analysed. Several academic papers were reviewed to understand the existing research and development efforts towards smart contract-based interoperability solutions. The ongoing discourse on blockchain interoperability is contributed to by highlighting the potential of smart contracts as bridge technologies, identifying key challenges and research gaps in this domain, and providing insights for further development of secure and efficient cross-chain communication protocols.